2019
DOI: 10.3390/biom9080326
|View full text |Cite
|
Sign up to set email alerts
|

β-Caryophyllene Mitigates Collagen Antibody Induced Arthritis (CAIA) in Mice Through a Cross-Talk between CB2 and PPAR-γ Receptors

Abstract: β-caryophyllene (BCP) is a cannabinoid receptor 2 (CB2) agonist that tempers inflammation. An interaction between the CB2 receptor and peroxisome proliferator-activated receptor gamma (PPAR-γ) has been suggested and PPAR-γ activation exerts anti-arthritic effects. The aim of this study was to characterize the therapeutic activity of BCP and to investigate PPAR-γ involvement in a collagen antibody induced arthritis (CAIA) experimental model. CAIA was induced through intraperitoneal injection of a monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 36 publications
(42 reference statements)
1
60
0
Order By: Relevance
“…In this experimental approach, U373 cells highly expressed NF-κB, whereas BCP treatment significantly reduced its expression. In addition, previous studies have indicated a possible crosstalk between the CB2 receptor and PPAR-γ [12,20]. The PPAR-γ receptor activation reduces pro-inflammatory cytokine release, thus exerting an anti-inflammatory effect [21].…”
Section: Discussionmentioning
confidence: 97%
“…In this experimental approach, U373 cells highly expressed NF-κB, whereas BCP treatment significantly reduced its expression. In addition, previous studies have indicated a possible crosstalk between the CB2 receptor and PPAR-γ [12,20]. The PPAR-γ receptor activation reduces pro-inflammatory cytokine release, thus exerting an anti-inflammatory effect [21].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it has been characterized by a plethora of biological activities, among which analgesic, anti-inflammatory, antioxidant, neuroprotective, and antiproliferative were the most investigated; moreover, it has been reported to affect phospholipid cooperativity and membrane permeability ( Table 3 ). These properties have provided benefits in several experimental models of disease, such as neurodegeneration, inflammation, pain, anxiety, depression, autoimmune diseases, metabolic ailments, osteoarthritis and some cancer models [ 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ,…”
Section: Caryophyllane Sesquiterpenesmentioning
confidence: 99%
“…Such benefits have been usually ascribed to the ability of β-caryophyllene to selectively activate the cannabinoid CB2 receptors (CB2Rs) [ 123 , 124 , 128 , 139 , 149 , 153 , 213 ], and to modulate further targets in the endocannabinoidome (i.e., the endogenous lipid signaling system including several fatty acid-derived mediators and their receptors, and their metabolic enzymes), such as the peroxisome proliferator-activated receptors (PPARs) and the fatty acid amide hydrolase (FAAH), which is a degrading enzyme of the endocannabinoid neurotransmitters [ 123 , 124 , 128 , 214 ]. Interestingly, a peripheral release of endogenous opioids seems to mediate the antinociceptive effects of β-caryophyllene, although nonpsychoactive responses have been also described [ 124 ].…”
Section: Caryophyllane Sesquiterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoids are known to interact or crosstalk with a family of peroxisome proliferated activator receptors (PPARs) including three distinct subtypes namely PPAR-α, PPAR-β/δ, and PPAR-γ that are encoded by distinct genes and are regulated by steroids and lipid metabolites and control lipid and glucose homeostasis and inflammatory responses [ 40 , 65 , 67 , 68 ]. The activation of CB2R on the surface of the cells triggers the intracellular signaling cascade that leads to the activation of PPARs [ 69 ]. The PPARs belongs to the members of nuclear receptor superfamily that functions as ligand-activated transcription factors and plays significantly in cellular proliferation, differentiation, organogenesis, inflammation, as well as the expression of hepatic enzymes regulating glucose homeostasis, insulin sensitivity, and lipid metabolism [ 70 ].…”
Section: Effects and Possible Mechanisms Of Bcp On Diabetesmentioning
confidence: 99%